The China-US trade dispute in Neo-Realism perspective and settlement of dispute by the WTO - Farnillah, Annisa Nadya; Paksi, Arie (Universitas Islam Malang, 2023)
This study examines the trade dispute between the United States and China from a neo-realist perspective. The relationship between the United States (US) and China became a public concern during the leadership of US President Donald Trump. How could it not be, the two countries were involved in a trade war which ultimately had an impact on the global trade sector in 2019. The method used in this research is qualitative, qualitative provides an in-depth explanation of a phenomenon by collecting related data, highlighting the importance of accuracy and detail in the information provided. studied. The aim of this research is to analyze the trade conflict between China and the US from a neo-realism perspective. This aim can help understand how power can influence. The research results show that the trade war started because Trump did not agree with his country's trade. then linked to neo realism where each country will respond based on its own aspirations for the sake of national interests. Until finally this trade dispute was resolved by the World Trade Organization (WTO). The WTO says the United States has violated global trade rules by imposing tariffs worth billions of dollars in its trade war with China. The WTO decision immediately angered Washington.